Safety of brigatinib following alectinib-induced-pneumonitis: Case report - Blerina Resuli; Heidi Galarza; Laura Elsner; Diego Kauffmann-Guerrero; Jürgen Behr; Amanda Tufman (Respiratory Medicine Case Reports)
Anaplastic lymphoma kinase tyrosine kinase inhibitors (ALK TKIs) show robust efficacy and has revolutionized the treatment of NSCLC patients harboring an ALK-rearrangement. Side effects, sometimes even serious such as pneumonitis, can occur with ALK TKIs.We report a case of a patient with ALK positive advanced NSCLC who developed pneumonitis during treatment with first-line alectinib. With no alternative etiology of pneumonitis identified, the patient was treated with corticosteroids and discontinuation of alectinib. Following rapid clinical recovery and radiographic resolution of the opacities, the patient was started with brigatinib, with no recurrence of the clinical symptoms or radiographic findings of pneumonitis. While further descriptions are needed, our experience suggests that switching to a second ALK-TKI may be a safe therapeutic option in some patients who develop drug-induced pneumonitis on ALK TKIs.